Penguatan Literasi Hukum Kesehatan melalui Media Digital bagi Remaja di Kelurahan Sriwedari dalam Mendorong Perilaku Hidup Sehat - Aris Prio Agus Santoso; Atsarina Luthfiyyah; Asyraf Mohamad Qhalish (Eastasouth Journal of Effective Community Services, 2026)
The rapid growth of digital technology has increased adolescents’ exposure to health misinformation, which is worsened by low legal health literacy. This community service program focuses on strengthening legal health literacy through digital media among adolescents in Sriwedari Village, Surakarta. The program aimed to improve adolescents’ understanding of health rights, legal protection, and healthy behavior. The method applied was Participatory Action Research involving 30 adolescents aged 13–17 years, conducted at the Sriwedari Village Library on March 31, 2026. Learning strategies included brainstorming, mind mapping, and the Think-Pair-Share method. The results showed a significant improvement in participants’ legal health literacy, increasing from 26.7% before the program to 80% after the program. Behavioral changes also emerged, such as increased awareness of legal health services, critical attitudes toward digital health information, the formation of youth health discussion groups, and the emergence of local youth leaders. This program proves effective in fostering sustainable legal health awareness among adolescents.